Respuesta :

-3(y + 5) + 3(2y + 6)
-3y - 15 + 6y + 18
3y + 3

Answer:
3y + 3

Hope this helps.
Hey there! 

In order to find the answer to this question you can do the distributive property to solve this particular problem

[tex]-3(y) = -3 \\ \\ -3(5) = 15 \\ \\ -3y + (-15) \\ \\ \\ \\ 3(2y) = 6y \\ \\ 3(6) = 18 \\ \\ \\ \\ \\ -3y + -15 + 6y + 18 [/tex]

Once when we do the distributive property we move onto the like terms 

Our Like terms: [tex]-3y + 6y \\ and \\ -15 + 18 [/tex]

So, lets solve our like terms 

[tex]-3y + 6y = 3y \\ \\ \\ -15 + 18 = 3 [/tex]

Finally!  we came to our answer

[tex]Answer: 3y + 3 [/tex]

Good luck on your assignment and enjoy your day 

~
[tex]LoveYourselfFirst:)[/tex]
ACCESS MORE